2002
DOI: 10.1073/pnas.192138799
|View full text |Cite
|
Sign up to set email alerts
|

A conserved mechanism for extracellular signaling in eukaryotes and prokaryotes

Abstract: Epidermal growth factor receptor (EGFr) is a key mediator of cell communication during animal development and homeostasis. In Drosophila, the signaling event is commonly regulated by the polytopic membrane protein Rhomboid (RHO), which mediates the proteolytic activation of EGFr ligands, allowing the secretion of the active signal. Until very recently, the biochemical function of RHO had remained elusive. It is now believed that Drosophila RHO is the founder member of a previously undescribed family of serine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 31 publications
0
78
0
Order By: Relevance
“…In the bacterium Providencia stuartii, cleavage of a small inhibitory N-terminal peptide from the twin-arginine translocase TatA by the rhomboid protease AarA initiates quorum sensing by activating TatA's function as a channel for export of the quorumsensing signal [30,31]. Interestingly, most bacteria do not encode a TatA protein with an N-terminal extension and therefore do not have to be activated by cleavage, suggesting that the role of AarA is a rare adaptation rather than a general mechanism (reviewed in [32]).…”
Section: Role In Signallingmentioning
confidence: 99%
“…In the bacterium Providencia stuartii, cleavage of a small inhibitory N-terminal peptide from the twin-arginine translocase TatA by the rhomboid protease AarA initiates quorum sensing by activating TatA's function as a channel for export of the quorumsensing signal [30,31]. Interestingly, most bacteria do not encode a TatA protein with an N-terminal extension and therefore do not have to be activated by cleavage, suggesting that the role of AarA is a rare adaptation rather than a general mechanism (reviewed in [32]).…”
Section: Role In Signallingmentioning
confidence: 99%
“…Despite significant sequence divergence, many rhomboid enzymes from both prokaryotes and eukaryotes share biochemical characteristics (14,15). The first rhomboid enzyme was discovered in Drosophila and functions in cleaving transmembrane epidermal growth factor ligands including Spitz to initiate signaling, but bacterial forms also can cleave Spitz (15,16). Mechanistic analyses revealed that Spitz is recognized by diverse rhomboid enzymes through the upper seven residues of its transmembrane domain, termed the Spitz substrate motif (14).…”
mentioning
confidence: 99%
“…In Drosophila, rhomboid proteins cleave the transmembrane domain of the epidermal growth factor receptor ligands, thereby releasing them to activate signaling (10). Drosophila Rhomboid-1 and AarA are able to functionally substitute for each other, indicating that the specificity of these rhomboids has been conserved across evolution (11). However, despite these similarities, the physiological substrate of AarA and the mechanism mediating AarA-dependent quorum-sensing in Prov.…”
mentioning
confidence: 99%